Agresja fizyczna i relacyjna. Wprowadzenie do różnic pomiędzy płciami - Andraszczyk, Wojciech; Gierczyk, Marcin (Studia Edukacyjne, 2020)
This article attempts a preliminary analysis of physical and relational aggression in the context of gender. The study of literature on the subject shows that the relations between gender and the above types of aggression are complex and fitperfectly the debate between proponents of biological determinism and social constructivism. It is difficultto derive a conclusion from both the results of empirical research on this problem and theoretical considerations, which are often ideology-dependent.